Effect of Ondansetron on the Occurrence of Hypotension and on Neonatal Parameters during Spinal Anesthesia for Elective Caesarean Section: A Prospective, Randomized, Controlled, Double-Blind Study - Walid Trabelsi; Chihebeddine Romdhani; Haythem Elaskri; Walid Sammoud; Mohamed Bensalah; Iheb Labbene; Mustapha Ferjani (Anesthesiology Research and Practice)
To prevent hypotension during spinal anesthesia for caesarean section, we assessed IV ondansetron of invasive maternal hemodynamic and fetal gazometric parameters.